Impact of Rural Grid-Connected Photovoltaic Generation Systems on Power Quality - Pinto, Rita (2019)
Photovoltaic (PV) generation systems have been increasingly used to generate electricity from renewable sources, attracting a growing interest. Recently, grid connected PV micro-generation facilities in individual homes have increased due to governmental policies as well as greater attention by industry. As low voltage (LV) distribution systems were built to make energy flow in one direction, the power feed-in of PV generation in rural low-voltage grids can influence power quality (PQ) as well as facility operation and reliability. This paper presents results on PQ analysis of a real PV generation facility connected to a rural low-voltage grid. Voltage fluctuations and voltage harmonic contents were observed. Statistical analysis shows a negative impact on PQ produced by this PV facility and also that only a small fraction of the energy available during a sunny day is converted, provoking losses of revenue and forcing the converter to work in an undesirable operating mode. We discuss the disturbances imposed upon the grid and their outcome regarding technical and economic viability of the PV system, as well as possible solutions. A low-voltage grid strengthening has been suggested and implemented. After that a new PQ analysis shows an improvement in the impact upon PQ, making this facility economically viable.